2010
DOI: 10.1111/j.1365-2427.2010.02492.x
|View full text |Cite
|
Sign up to set email alerts
|

Light, nutrients and grazing interact to determine stream diatom community composition and functional group structure

Abstract: 1. Benthic algal communities are shaped by the availability of nutrients and light and by herbivore consumption. Many studies have examined how one of these factors affects algal communities, but studies simultaneously addressing all three are rare. 2. We investigated the effects of nutrients, light and a herbivore (the snail Potamopyrgus antipodarum) on benthic stream algae in a fully factorial experiment in 128 circular streamside channels. Four nutrient levels (none added to highly enriched), four snail gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
134
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 51 publications
11
134
3
Order By: Relevance
“…These reductions in direct sunlight monitored within the flumes were closely comparable with those observed under partial and full tree canopy (Table 4). Shading was also found to reduce the proportion of motile diatoms in a recirculating flume study by Lange et al, (2011). As in the current study (Figure11), the motile diatom Nitzschia palea was less abundant in the shaded treatments, whereas the adnate diatoms…”
Section: Effect Of Light Intensity On Periphytonsupporting
confidence: 76%
See 1 more Smart Citation
“…These reductions in direct sunlight monitored within the flumes were closely comparable with those observed under partial and full tree canopy (Table 4). Shading was also found to reduce the proportion of motile diatoms in a recirculating flume study by Lange et al, (2011). As in the current study (Figure11), the motile diatom Nitzschia palea was less abundant in the shaded treatments, whereas the adnate diatoms…”
Section: Effect Of Light Intensity On Periphytonsupporting
confidence: 76%
“…Cocconeis placentula and Achnanthidium minutissimum occurred at higher abundances under reduced light (Lange et al, 2011). Motile diatoms are generally at an advantage within thick biofilms (e.g.…”
Section: Effect Of Light Intensity On Periphytonmentioning
confidence: 99%
“…The occurrence of benthic diatoms in streams is the outcome of complex interactions between abiotic factors, such as hydrological and chemical, and biotic factors (Stevenson et al, 1996;Lange et al, 2011). Local environmental variables that may influence diatom communities include water chemistry, current velocity, light, grazing, temperature and substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Of the local proximate factors, water chemistry and amount of light are often the most important variables influencing the density of diatom populations (Stevenson et al, 1996;Lange et al, 2011). Temperature interacts with these variables to affect the rates of metabolism and growth.…”
Section: Introductionmentioning
confidence: 99%
“…They also concluded that as the number of stressors in a system increase, stressor pair interactions become increasingly complex and more commonly synergistic. In laboratory settings, few studies have been conducted that analyze the responses of the diatom assemblage to the effects of multiple A c c e p t e d M a n u s c r i p t variables combined (such as Navarro Rodriguez, 1998;Rier & Stevenson, 2002;Lange et al, 2011), a situation that is more likely to occur in a natural stream since environmental changes rarely affect a single variable.…”
Section: Introductionmentioning
confidence: 99%